The association of psychiatric comorbidity and use of the emergency department among persons with substance use disorders: an observational cohort study - Curran, Geoffrey M (BioMed Central, 2008)
BACKGROUND: Psychiatric and substance use problems are commonly found to be contributing factors to frequent Emergency Department (ED) use, yet little research has focused on the association between substance use and psychiatric comorbidity. This study assesses the association of a psychiatric comorbidity on (ED) use among patients with substance use disorders (SUDs). METHODS: The study focuses on 6,865 patients who were diagnosed with SUDs in the ED of a large urban hospital in the southern United States from January 1994 – June 1998. Patients were grouped by type of substance use disorder. After examining frequency of visits by diagnosis, the sample was assigned to the following groups–alcohol dependence (ICD9 = 303), alcohol abuse (ICD9 = 305.0), cocaine dependence/abuse (ICD9 = 304.2, 305.6), and polysubstance/mixed use (ICD9 = 305.9). A patient was classified with psychiatric comorbidity if a psychiatric diagnosis appeared during any of the patient's visits. The following psychiatric diagnoses were included–schizophrenia/psychoses, bipolar disorder, depression, anxiety, and dementia (ICD-9 codes available upon request). RESULTS: Patients with SUDs and psychiatric comorbidity had significantly higher mean number of ER visits (mean = 5.2 SD = 8.7) than SUD patients without psychiatric comorbidity (mean = 2.5, SD = 3.7). In logistic regressions predicting several categorizations of heavier use of the ED (either 4+, 8+, 12+, 16+, or 20+ visits over the span of the study) SUD patients with psychiatric comorbidity had adjusted odds ratios of 3.0 to 5.6 (reference group = patients with SUDs but no psychiatric comorbidity). This association was found across all substance use diagnostic categories studied, with the strongest relationship observed among patients with cocaine disorders or alcohol dependence. CONCLUSION: The results provide further support for the notion that the ED could and should serve as an important identification site for cost-effective intervention.